Promoting Diversity and Inclusion in Surgical Societies: Representation Matters. Issue 5 (4th May 2021) - Sutherland, Mason; Sen-Crowe, Brendon; McKenney, Mark; Elkbuli, Adel
Abstract : Supplemental Digital Content is available in the text